Robust anti-tubercular profile of Solanum virginianum extract in enhancing isoniazid bioavailability and curtailing stress tolerance in Mycobacterium smegmatis - Balkrishna, Acharya; Joshi, Monali; Kabdwal, Manisha; Tomer, Meenu; Lochab, Savita; Varshney, Anurag (Frontiers in Microbiology, 2024)
Introduction The formidable survival mechanisms employed by Mycobacterium tuberculosis (Mtb), combined with the low bioavailability of anti-tubercular drugs and their associated hepatotoxicity, worsen tuberculosis management. Traditional medicinal plants offer potential solutions to these challenges. This study focuses on exploring the anti-tubercular potential of Solanum virginianum against Mycobacterium smegmatis, mc2155. Methods and results HPTLC and UHPLC phytochemically characterized the hydro-methanolic extract of Solanum virginianum (SVE). SVE curtails the growth and viability of mc2155 under normal and in vitro stress conditions. The compromised cell wall integrity of mc2155 with SVE is depicted through scanning electron microscopy (SEM) while EtBr permeability assays and TLC-based comparative changes in lipids extraction addressed the integrity of the cell wall. Furthermore, SVE augmented the susceptibility of mc2155 towards Isoniazid (INH) through enhanced bioavailability. Adjunct treatment of SVE with INH demonstrated a markedly reduced survival of the intracellular bacilli. The study also uncovered the hepatoprotective potential of SVE in HepG2 cells. Conclusion This research paves the way for deeper exploration into the potential of Solanum virginianum against virulent Mtb strains, emphasizing over the significance of traditional medicinal plants in tuberculosis treatment. Collectively, the findings suggest SVE as a potent candidate for independent or adjunct anti-tubercular therapy.